(untitled) (Journal of Science and Technology, 2016)
Ghana currently operates a Research Reactor, a Gamma Irradiation Facility, a Radiotherapy Centre and a Radiographic Non-Destructive Testing Laboratory. Each of these facilities has- a concrete radiation shield as a major safety device. Inevitably, a concrete radiation shield in performing its functions is subjected to nuclear heating. Beyond certain limits this phenomenon can have deleterious effects upon the performance of the shield. This paper discusses the evaluation of the stresses resulting from the nuclear heating of a concrete radiation shield using a computer code named "NUCLAS. Results of these stresses as obtained from NUCLAS on the analysis of the Ghana Research Reactor I (GHARR-I) are presented.